ANALYZING WIND SPEED DISTRIBUTION ACROSS RECTANGULAR ROADWAY ANEMOMETER STATIONS WITH LDA - Petrova, Sofia (Ayden International Journal of Basic and Applied Sciences, 2024)
Efficient and accurate measurement of mine ventilation parameters is essential for ensuring the safety of coal mines. However, the turbulent nature of airflow in underground coal mines poses significant challenges to obtaining precise measurements of parameters like wind speed. Current measurement methods in Chinese coal mines combine manual measurements and real-time monitoring with wind speed sensors. Manual measurements are labor-intensive and subject to uncertainty, while real-time sensor systems may not capture accurate average wind speeds due to improper sensor positioning. This paper addresses these challenges by using Laser Doppler Anemometer (LDA) technology to measure wind speeds in a controlled laboratory setup, avoiding interference with fluid flow